PENGARUH MODEL MIND MAPPING TERHADAP HASIL BELAJAR IPS DI SD - Devy Pradipta; Sugiyono Sugiyono; Hamdani Hamdani (Universitas Tanjungpura, 2019)
AbstractThis research aimed to analyze the effect of model Mind Mapping against learning outcomes Social Science grade V 66 Country elementary school City of Pontianak. The methods used in this research was a method of experimentation. Experimental design Nonequivalent Control Group Design. The population in this research was the entire grade of the sample selection Technique was Simple Random Sampling. Sample research VA class as experiments and VB class as control. Data collecting technique used in this research was measurement technique. Data collecting tool in the form of test results of student learning. The study resulted average post test experimental 80.19 and class results average learning post test control 72.78 class. After analyzed by t-test acquired t count amounted to 3.322 and t α = 5% table (with dk = 32 + 32 – 2 = 62) of 1.994, meaning t count (3.322) > t table (1.994), the Ha received. So it can be concluded that there was a Mind Mapping model of influence against the learning outcomes Social Science grade V 66 Country elementary school City of Pontianak. The calculation of effect size (ES), retrieved the ICE of 0.81. This means that Mind Mapping model gave effect to the results of student learning. Keywords : Mind Mapping Model, The Results Of The Study, The Social Science.